The Demarcation Problem: Karl Popper’s solution in the contemporary retrospective - Sepetyi, D. P.; Сепетий, Дмитро Петрович (My University, 2024)
Abstract. The article analyses post-Popperian debates about the problem of demarcation. The case is made that Karl Popper’s proposition to demarcate empirical science from the rest («metaphysics») on the basis of falsifiability as the criterion of empirical character of theories remains a tenable way of seeing the most valuable aspect of the character of the scientific enterprise. It is explained that for the falsifiability criterion to be adequate for the purpose, we should consider it, as Popper did, as two-aspect — involving the logical content of theories and the critical attitude of researchers. Although falsifiability, in this sense, is not sufficient to neatly demarcate science from non-science, it can be considered as the most important necessary condition, which can be supplemented by some further requirements, for an empirical hypothesis to count as part of the body of science. In particular, it is argued that Lee McIntyre’s proposition to see empirical science as a matter of what he calls «scientific attitude» perfectly fits with this falsifiability-based perspective. William Bartley’s and Harry Laudan’s deflationary approaches to the demarcation problem are criticised as failing to recognise the practical significance of distinguishing what is and what is not empirical science, and the necessity of some theoretical grounding (however imperfect) for practicing this distinction. The suggestions of Joseph Agassi, Imre Lakatos, and Thomas Kuhn purported at the improval of Popper’s demarcational proposition are discussed, and the author’s own proposition is advanced and explained. It is also pointed out that Popper’s remark that the distinctive feature of scientific theories is openness to criticism and modification in its light serves as the basis for a wider conception of science, without the qualification «empirical». У статтi проаналiзовано постпопперiвськi дебати щодо проблеми демаркацiї. Обґрунтовано думку, що пропозицiя Карла Поппера вiдмежовувати емпiричну науку вiд решти («метафiзики») на основi фальсифiкабельностi як критерiю емпiричного характеру теорiй залишається доречним способом бачення найбiльш цiнного аспекту характеру наукової дiяльностi. З’ясовано, що для того, щоб критерiй фальсифiкабельностi був адекватним поставленiй метi, його слiд розглядати, як це робив Поппер, як двоаспектний, що включає логiчний змiст теорiй та критичне ставлення дослiдникiв. Хоча фальсифiкабельнiсть у цьому сенсi не є достатньою для чiткого розмежування науки i ненауки, її можна розглядати як найважливiшу необхiдну умову, яка може бути доповнена деякими iншими вимогами для того, щоб емпiрична гiпотеза могла вважатися науковою. Зокрема, показано, що пропозицiя Лi Макiнтайра розглядати емпiричну науку як таку, що визначається описаною ним «науковою настановою», цiлком вписується в цю фальсифiкацiйну перспективу. Пiддано критицi дефляцiйнi пiдходи до проблеми демаркацiї Вiльяма Бартлi та Гаррi Лаудана, як такi, що не вiдповiдають практичнiй значущостi розрiзнення того, що є i що не є емпiричною наукою, а також необхiдностi теоретичного обґрунтування цiєї розрiзнювальної практики, хоча б i недосконалого. Обговорено пропозицiї Джозефа Аґассi, Iмре Лакатоша та Томаса Куна, спрямованi на вдосконалення демаркацiйної пропозицiї Поппера, а також запропоновано i пояснено власну пропозицiю автора. Також зазначено, що зауваження Поппера про те, що визначальною рисою наукових теорiй є вiдкритiсть до критики та модифiкацiї в її свiтлi, може слугувати основою для ширшої концепцiї науки, без квалiфiкацiї «емпiрична».
Keywords: demarcation; falsification; science; empirical; metaphysics; pseudoscience; демаркацiя; фальсифiкацiя; наука; емпiричний; метафiзика; псевдонаука